Enol-imino−Keto-enamine Tautomerism in a Diazepine Derivative: How Decisive Are the Intermolecular Interactions in the Equilibrium? - Rocha, Mariana (2019)
The strange tautomeric equilibrium behavior exhibited by a new o-hydroxyphenyl diazepine derivative when the compound is analyzed both in solution and solid state opens the structural study of the enol-imino-keto-enamine forms and the influence of the intermolecular interactions in their equilibrium. The expected enol-imino form, in which the enol is part of a phenyl system and a strong O-H···N intramolecular hydrogen bond is established, results the most stable tautomer in gas phase (theoretical calculations) and was detected by NMR spectroscopy when the compound was dissolved in aprotic solvents. Nevertheless, the keto-enamine form, in which the keto group integrates a cyclohexadienone moiety and the aromaticity of the phenol is lost, was the only tautomer in the crystal lattice according to single-crystal X-ray diffraction, vibrational spectroscopy, and diffuse reflectance results. The last form was also found as the main tautomer in UV-vis and NMR spectroscopy when a protic solvent was employed.